EXPERIMENTAL PARACOCCIDIOIDOMYCOSIS IN PREGNANT RATS - Eduardo Alexandre LOTH; Vanessa CECATTO; Samia Khalil BIAZIM; José Henrique Fermino FERREIRA; Caroline DANIELLI; Rodrigo Daniel GENSKE; Rinaldo Ferreira GANDRA; Marcello Fabiano de FRANCO (Revista do Instituto de Medicina Tropical de São Paulo, 2015)
Paracoccidioidomycosis (PCM), caused by the dimorphic fungus Paracoccidioides brasiliensis (Pb), is the most prevalent systemic mycosis in Latin America. There are few reports in the literature about the disease damages during pregnancy and the consequences to the fetuses and breeding. This study evaluated the implications of PCM during pregnancy on offspring and mothers in Wistar rats. Groups of rats were submitted to systemic Pb infection, by intraperitoneal infusion, and mated 30 days after the infection date. Immediately after birth, rats and neonates were sacrificed to obtain organs for standard histological examination, morphometric analysis, fungi recovery by plating (CFU) and dosing of anti-Pb antibodies by ELISA. There were no stillbirths or miscarriages, however, the fetuses from infected pregnant rats had lower body and organ weight but the fertility rate was 100%. The largest number of CFU was recovered from the organ of pregnant rats, the pathological examination revealed more severe infection in the same group, further on the largest number of granulomas and fungal field. It can be concluded that the PCM was more severe in the group of pregnant rats, with implications to the weight of offspring.